PROPOSAL STUDY DESERT FOREST NEAR ES-SIDER OIL PORT NW LIBYA - Elosta, Fathi (MATTER: International Journal of Science and Technology, 2015)
Located that oil port of siders following waha Oil Company which is located west of sirt on covering the moving sand dunes pot dominated system desertification. The solar energy will be used to evaporated brine and generate cool air pure water in order to grow food inside the greenhouses where the sea water will be used facilities. Concentrated idea of the project to exploit an area of about 20km through which pipeline to flow of sea water to the ground which may allow the lows of Nature which produce fresh water from sea water and change climate conditions to humid climate contributes to the rainfall and characterized the technology that will be used in the project to its ability to transform large tracts of desert into green produce commercial quantities of food and energy crops and freshwater used the project is based on the establishment of greenhouse where sea water used provide growth conditions cold and wet of vegetables in addition to the production of fresh water and will be connected to the solar with thermal units for the desalination of sea water supported by technology and will allow pilot also cultivation of algae in the system of bioreactors optical and farming systems in basins exposed produces plant food ,water, energy between greenhouse protected salt water and solar power intensive and cultivation of algae and technological and scientific . the basic idea of this project is to bring sea water into the desert then vaporized process centered on what is known as sea water where the evaporating sea water by solar energy and then intensify freshwater not only that but maintains a moist interior cool and are ideal for the cultivation of crops ,it was the first model to sea water greenhouse a unit area of 2000 square meters in port Augusta in Australia and has won its first crop tomatoes in the last months ago ,Sahara forest project combines the technology and solar power uses mirrors to focus the light on the complex to heat which in turn produces steam for the management of turbine generator at a supplying greenhouse powered and operated and the greenhouse extended solar power plant with water marking them more efficient that the project is promising and important in the field of renewable energy and to take advantage of the potential and of solar energy in our integrated project and ambitious aims to cultivate bio-fuels to generate an energy clean aimed at protecting the environmental may work on climate change. The project is based on the new Technologies in carpeted into solar energy and seawater Greenhouse and cultivation of green algae and for the cultivation of arid areas and the provision of food and fresh water as well as bio-fuels to generate clean energy. The idea of the project is simple and Natural based on the use of solar energy in the evaporation of salty seawater to generate cold air and water and clean energy in deserts and Technology use Mirrors sunlight to form steam to Run turbines which in turn generate electricity is expected to shift the equipment desert to the territory to the a prosperous agricultural out about the need to drill water wells which increase water shortage and possible planting any kind of vegetables in greenhouse sea water are essential in the project which cost to be cooling desert air warm and ? Wet with sea water before being admitted to the greenhouse and this air humidifier will feed crops inside greenhouse then dryer where flowing sea water heated warmly sun? and soon meet air humidifies of channels containing water condenses fresh water and dripped drops on the external aspects of channels that can be assembled the process mimic what happens in Nature evaporates sea water as a result of the sun’s heat and work is underway to cooling leads to the formation of clouds and condense these vapors of water to fall water like rain only 10-15 % of moist air condenses into fresh water and the rest out of the surrounding tress thus the greenhouse creating green surroundings around the will be through energy intensive and through the use of Mirrors to focus sunlight on pipes and boilers for water district cause radiation intensive production high heat inside the pipe provides enough power to turn Turbines team which in turn would for electrical power and six cell additional power to the people are a population of benefiting says a specialist and is Neil Crompton one energy experts there is huge potential for these new Technologies unit focused and one covering only 9% of the area of deserts ground and can provide five global need for energy as well as can invest this technique streaming tons of sea water per day using only 20 thousand greenhouse.